Analysis of Neutral Polarization Points - Roziqov, J.; Zokirov, A. (Research Parks Publishing LLC, 2023)
Neutral polarization points (NPPs) and land-atmosphere parameter separation (LAPS) are crucial concepts in remote sensing and atmospheric science. NPPs indicate locations where incoming light loses its polarization due to the absence of a preferential direction, such as on lunar soil. LAPS involves separating land surface parameters, including vegetation, soil moisture, and temperature, from atmospheric effects in remote sensing data. Accurate separation of these parameters is vital for precise remote sensing of Earth's surface and climate change assessment. This article discusses the principles of NPPs and LAPS, their applications in remote sensing, and their significance in atmospheric science.